Securing ownership management and transfer of consumer IoT devices with blockchain-based Self Sovereign Identity (SSI) - Sakib, Nazmus; Mumu, Marzia Islam; Momo, Nuran Mubashshira (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.